A novel supramolecular architecture based on melamine and biphenyl-4, 4-dicarboxylic acid: Synthesis, crystal structure and luminescent property. (1st January 2019) - Liu, Ruichao; Liu, Jie; Yan, Xiangzhen; Yuan, Chunxue
Graphical abstract: A novel cocrystal [(HMA + )2 (BPDC 2− )]·4H2 O based on MA and H2 BPDC was synthesized under solvothermal conditions. Crystal structure analysis indicated that it has a 3D microporous structure which is constructed by hydrogen bonds (NH⋯O, NH⋯N, OH⋯O) and aromatic π⋯π interaction. And it possesses strong cyan fluorescence emission. Abstract: A novel cocrystal [(HMA + )2 (BPDC 2− )]·4H2 O (1 ) based on MA (melamine) and H2 BPDC (biphenyl-4, 4-dicarboxylic acid) was synthesized under solvothermal conditions. The supramolecular complex has been characterized by single crystal diffraction, infrared spectroscopy, elemental analysis and X-ray diffraction. Crystal structure analysis indicated that compound1 has a 3D microporous structure which is constructed by hydrogen bonds (NH⋯O, NH⋯N, OH⋯O) and aromatic π⋯π interaction. In addition, the thermal stability and luminescent property of1 were also investigated in detail.